Rapid degradation of the organophosphate pesticide – Chlorpyrifos by a novel strain of Pseudomonas nitroreducens AR-3. (November 2019) - Aswathi, Aswathi; Pandey, Ashok; Sukumaran, Rajeev K.
Highlights: P. nitroreducens AR-3 isolated from contaminated soil degrades 97% of chlorpyrifos. Chlorpyrifos degradation achieved in 8 h, fastest reported among Pseudomonads. An inducible organophosphate hydrolase is implicated for chlorpyrifos degradation. The organophosphate hydrolase could also effectively remove methyl parathion. Abstract: The indiscriminate use of pesticides leads to serious food safety and toxicity issues and threatens the environment and biodiversity. Pseudomonas nitroreducens AR-3 isolated from pesticide contaminated agricultural soil removed 97% of chlorpyrifos (CP) in just 8 h, in a mineral salt medium (MSM) containing glucose (1.0 g/L) and yeast extract (0.5 g/L) at 30 °C and 2% (v/v) inoculum when challenged with 100 mg/L CP. 3, 5, 6-trichloro 2-pyridinol (TCP), the degradation product of CP was detected only in low levels, indicating its further degradation. Organophosphate hydrolase (OPH), the enzyme considered responsible for CP degradation, had an intracellular localization. Crude OPH (1 mg/ml) removed 42% of 100 mg/L chlorpyrifos in just 2 h, indicating a rapid rate of degradation. Ultra-fast degradation of chlorpyrifos with an inducible OPH marks the potential of P. nitroreducens AR-3 for bioremediation of organophosphates. The strain AR-3 has the fastest rate of organophosphate degradation reported till date among Pseudomonads.